2003
DOI: 10.1080/1355621031000069882
|View full text |Cite
|
Sign up to set email alerts
|

Major disruptions of sleep during treatment of the opiate withdrawal syndrome: differences between methadone and lofexidine detoxification treatments

Abstract: Sleep disturbance experienced during methadone or lofexidine opiate detoxification was investigated in 118 opiate-dependent patients receiving inpatient detoxification treatment. Sleep was assessed at four time-points during opiate detoxification using a self-report questionnaire. Maximum sleep disruption occurred at completion of detoxification and during the protracted withdrawal period, with patients in the methadone group reporting higher levels of withdrawal symptoms, lower overall sleep, longer sleep lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 25 publications
0
27
0
2
Order By: Relevance
“…Sleep problems are a very common complaint from patients undergoing opiate detoxification treatment. The importance of addressing this issue is substantiated in a study by Bestwick et al 20 who found that in a population of 118 opiate/opioid dependent patients undergoing inpatient detoxification treatment, there was a significant inverse relationship between sleep disturbance and retention in treatment. As sleep disturbances increased in severity, retention rates decreased.…”
Section: Discussionmentioning
confidence: 92%
“…Sleep problems are a very common complaint from patients undergoing opiate detoxification treatment. The importance of addressing this issue is substantiated in a study by Bestwick et al 20 who found that in a population of 118 opiate/opioid dependent patients undergoing inpatient detoxification treatment, there was a significant inverse relationship between sleep disturbance and retention in treatment. As sleep disturbances increased in severity, retention rates decreased.…”
Section: Discussionmentioning
confidence: 92%
“…İlaç ve ruhsal-toplumsal tedavilere rağmen uyku bozuklukları, anksiyete ve depresif belirtiler bu hastalarda sık görülmektedir. 3,4 Literatürde opiyat bağımlılarında psikiyatrik eş tanı yaygınlığı %20-70 arasında bildirilmiştir. 5,6 Çalışmalarda opiyat bağımlılarında depresyon veya anksiyete bozukluğu eş tanısı olanların olmayanlara göre uyku kaliteleri daha kötü bulunmuştur.…”
Section: Introductionunclassified
“…8 OB'de, ilaç ve ruhsal-toplumsal tedavilere rağmen uyku bozuklukları sık görülmektedir. 3,7,11 Kronik reçeteli opiyat kullanan hastaların %80.6'sının uyku kalitesinin kötü olduğu bulunmuştur. 12 OB tedavisinde kullanılan metadon veya buprenorfin ile arındırma tedavisi yapılan hastaların uyku özelliklerinde bozulmalar ve farklılaşmalar olduğu, uyku latansının uzadığı ve uykunun fragmante olduğu saptanmıştır.…”
Section: Introductionunclassified
“…This measure is well suited as a behavioral tool to investigate the negative affective sequelae of opiate exposure for several reasons. First, the startle reflex can be measured repeatedly in the same subjects (Harris et al, 2004), making it suitable for studying within-subject changes of state across time (Beswick et al, 2003; Rounsaville et al, 1985). Second, the anatomical circuit mediating the startle reflex is relatively simple and well characterized (Lee et al, 1996; Nodal and Lopez, 2003), allowing circuitry involved in modulating startle during withdrawal to be more easily identified.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we measured plasma levels of the steroidal stress hormone corticosterone, as well as using startle to assess alterations in circadian rhythms. Both are common outcome measures of opiate withdrawal (e.g., Becker et al, 2008; Beswick et al, 2003; Li et al, 2010) and depression (for a review, see Kronfeld-Schor and Einat, 2012). …”
Section: Introductionmentioning
confidence: 99%